SWOT Analysis of the Economic Potential of Islamic Boarding Schools in Indonesia: NVivo Approach Study and Literature Review - Rohmadi Rohmadi; Doni Yusuf Bagaskara (Al-Kharaj: Journal of Islamic Economic and Business, 2023)
This research aims to determine a SWOT analysis regarding the economic potential of Islamic boarding schools in Indonesia using the NVivo approach. This research uses qualitative methodology with the NVivo approach and literature review. "Data analysis techniques include: (1) mapping the number of news article codes based on SWOT analysis, namely (strengths, weaknesses, opportunities and threats), regarding "Islamic Boarding School Economics" using NVivo 14 software; (2) map the visualization results with a hierarchical diagram and test the correlation between media articles using SWOT Analysis; (3) mapping research topics with Worldcloud or a collection of words that are often discussed in media articles; and (4) Testing the significant value between media articles to determine the size or size of the correlation around the topic "Islamic Boarding School Economics". The results of this research show that the topics often discussed in media articles regarding Islamic Boarding School Economics are challenges and opportunities. Meanwhile, a topic that is rarely discussed by media articles regarding Islamic Boarding School Economics is strengths and weaknesses. The implications of this research show that the resulting SWOT study and literature review provide recommendations for improving the management of Islamic boarding school-based economic potential in the future.